Assessment of Linkage Between Value Chain of Large Cardamom (Amomum subulatum, Roxburg) and Food and Nutritional Security in Bhojpur, Nepal. - Joshi, Arati. (Tufts University. Tisch Library., 2020)
This presentation explores the value chain of cardomom in Nepal and its relationship with food and nutritional security.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy